TEKNOLOGI BLOCKCHAIN PADA AUDIT FORENSIK: SOLUSI MENGATASI ANONIMITAS ATAU MENJADI TANTANGAN TEKNIS YANG SULIT DIIMPLEMENTASIKAN? - Melina Vaniatan; Rina Tjandrakirana DP (Cahaya Ilmu Bangsa, 2025)
Blockchain technology plays a pivotal role in forensic auditing by providing immutable and transparent records, thereby enhancing the detection and prevention of fraudulent activities. This study aims to identify the role and effectiveness of forensic audits in detecting suspicious transactions within the crypto ecosystem and to analyze the technical and regulatory challenges encountered during the implementation of forensic audits on crypto transactions. Employing a Systematic Literature Review (SLR) methodology, the research synthesizes findings from 30 prior studies sourced from Scopus, DOAJ, SINTA, SJR, CROSSREF, and Google Scholar. The results indicate that blockchain's transparency and immutability can bolster data integrity in forensic audits. However, without a comprehensive approach, the inherent anonymity of blockchain will continue to pose substantial obstacles in forensic audits within the financial and crypto sectors. Therefore, while blockchain holds significant potential to enhance audit efficiency and reliability, overcoming technical and regulatory hurdles is essential to fully leverage its benefits in forensic contexts.